A case of hospital-acquired pneumonia associated with Chryseobacterium indologenes infection in a patient with HIV infection and review of the literature - Vincenza Chiara Mazzola; Eleonora Bono; Luca Pipitò; Benedetta Romanin; Claudia Gioè; Antonio Anastasia; Sara Cannella; Roberta Virruso; Celestino Bonura; Antonio Cascio (AIDS Research and Therapy)
Abstract Background Chryseobacterium indologenes is an opportunistic, multidrug-resistant Gram-negative bacillus increasingly recognized as a cause of hospital-acquired infections, particularly in immunocompromised patients. Although rare, its intrinsic resistance to beta-lactams and its ability to colonize medical devices pose significant therapeutic challenges. Case Presentation We describe a case of C. indologenes hospital-acquired pneumonia in a 43-year-old HIV-positive patient with multiple comorbidities, including Kaposi sarcoma, diabetes mellitus, and chronic kidney disease requiring hemodialysis. The patient was initially admitted with fever and elevated inflammatory markers, and empirical broad-spectrum antibiotic therapy was initiated. Despite initial improvement, the patient developed respiratory failure, requiring oxygen therapy. A respiratory panel identified Rhinovirus, while sputum culture revealed C. indologenes, resistant to multiple antibiotics but susceptible to levofloxacin. Targeted therapy led to clinical improvement. However, the course was complicated by Clostridioides difficile-associated diarrhea, followed by fatal sepsis due to Klebsiella pneumoniae. Our review of the literature identified 71 reported cases, with bacteremia (51%) and pneumonia (29%) as the most common clinical presentations. Medical devices and prolonged antibiotic exposure were key risk factors. While C. indologenes is intrinsically resistant to beta-lactams and carbapenems, fluoroquinolones and trimethoprim-sulfamethoxazole demonstrated efficacy in most cases. Emerging therapies, such as cefiderocol, may provide additional options for multidrug-resistant strains. This case highlights the critical need for accurate microbial identification, targeted therapy, and vigilant antimicrobial stewardship to improve outcomes in vulnerable patient populations. Conclusion C. indologenes infections remain rare but clinically significant in hospitalized patients with immune dysfunction. The pathogen’s multidrug resistance profile complicates treatment, necessitating early identification and targeted antimicrobial therapy. Fluoroquinolones, trimethoprim-sulfamethoxazole, and cefiderocol may serve as effective treatment options, emphasizing the importance of susceptibility-guided management.